1985
DOI: 10.7326/0003-4819-102-5-623
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Human T-Lymphotropic Virus Type III in Wives of Hemophiliacs

Abstract: To evaluate the risk of heterosexual transmission of the acquired immunodeficiency syndrome, lymphadenopathy, and infection with human T-lymphotropic virus type III (HTLV-III), we studied 42 hemophiliacs and their wives. By early 1984, 9 of the hemophiliacs had asymptomatic lymphadenopathy and 1 had the acquired immunodeficiency syndrome. Twenty-one hemophiliacs, including all 10 with clinically overt disease, had antibody to HTLV-III. None of the 42 wives had lymphadenopathy or the acquired immunodeficiency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Studies of female partners of men with acquired immunodeficiency syndrome (AIDS) or AIDSrelated conditions (ARC) have found high seropositivity rates, from 36 per cent to 71 per cent,9l1 whereas studies of mostly asymptomatic female partners of seropositive hemophiliacs report much lower rates, from 7 per cent to 15 per cent. [12][13][14] The differences in apparent transmission of HIV in these studies are difficult to explain by sexual practices alone and suggest variation in the infectiousness of the HIV carrier or in the susceptibility to infection of the partner. We report here on an analysis of risk factors for seropositivity to HIV antibody in a group of homosexual men who were regular sexual partners of men who developed AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of female partners of men with acquired immunodeficiency syndrome (AIDS) or AIDSrelated conditions (ARC) have found high seropositivity rates, from 36 per cent to 71 per cent,9l1 whereas studies of mostly asymptomatic female partners of seropositive hemophiliacs report much lower rates, from 7 per cent to 15 per cent. [12][13][14] The differences in apparent transmission of HIV in these studies are difficult to explain by sexual practices alone and suggest variation in the infectiousness of the HIV carrier or in the susceptibility to infection of the partner. We report here on an analysis of risk factors for seropositivity to HIV antibody in a group of homosexual men who were regular sexual partners of men who developed AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Kreiss et al (1985) studied 42 haemophiliacs and their wives between the end of 1982 and early 1984. Twenty-one of the haemophiliacs were HIV positive and, at the end of the study period, 2 of their wives were also HIV positive.…”
Section: Accidentsmentioning
confidence: 99%
“…In 1984 the first reports on AIDS [28] and lymphadenopathy [30] in female sexual partners of hemophiliacs were published. After serological tests for HIV had become available, various groups investigated the seroprevalence of HIV in sexual partners of hemophiliacs [15], [18], [22], [2], [3], [14], [23], [6], [13], [24]. In all the different studies about 10% of the heterosexual partners of hemophiliacs were shown to be infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Both HIV infection [18] and AIDS [28] were documented in female sexual partners of hemophiliacs only shortly after the beginning of the AIDS epidemic. The aim of our study is to determine the rate of heterosexual HIV-transmission in our hemophilic patients, to determine the clinical course of those infected, and to define possible risk factors associated with the heterosexual transmission of HIV.…”
Section: Abstract: Hemophilia -Human Immunodeficiency Virus -Heterosmentioning
confidence: 99%